Novel domains and orthologues of eukaryotic transcription elongation factors. - Ponting, C (2002)
The passage of RNA polymerase II across eukaryotic genes is impeded by the nucleosome, an octamer of histones H2A, H2B, H3 and H4 dimers. More than a dozen factors in the yeast Saccharomyces cerevisiae are known to facilitate transcription elongation through chromatin. In order to better understand the evolution and function of these factors, their sequences have been compared with known protein, EST and DNA sequences. Elongator subcomplex components Elp4p and Elp6p are shown to be homologues of ATPases, yet with substitutions of amino acids critical for ATP hydrolysis, and novel orthologues of Elp5p are detectable in human, and other animal, sequences. The yeast CP complex is shown to contain a likely inactive homologue of M24 family metalloproteases in Spt16p/Cdc68p and a 2-fold repeat in Pob3p, the orthologue of mammalian SSRP1. Archaeal DNA-directed RNA polymerase subunit E" is shown to be the orthologue of eukaryotic Spt4p, and Spt5p and prokaryotic NusG are shown to contain a novel 'NGN' domain. Spt6p is found to contain a domain homologous to the YqgF family of RNases, although this domain may also lack catalytic activity. These findings imply that much of the transcription elongation machinery of eukaryotes has been acquired subsequent to their divergence from prokaryotes.